Patient Satisfaction with Outpatient Cervical Ripening in Parous Women - Wang, Michelle J.; Jauk, Victoria C.; George, David M.; Kuper, Spencer G.; Edwards, Rodney K.; Szychowski, Jeff M.; Mazzoni, Sara E.; Files, Pamela; Tita, Alan T.; Subramaniam, Akila; Harper, Lorie M. (American Journal of Perinatology, 2020)
Objective This study aimed to assess whether patient satisfaction differs between women beginning cervical ripening in the outpatient versus inpatient setting.Study Design We performed a planned secondary analysis evaluating patient satisfaction randomized to outpatient versus inpatient cervical ripening. In the original randomized controlled trial, low-risk parous women ≥39 weeks who required cervical ripening for induction and had reassuring fetal heart rate monitoring were included and randomized to inpatient versus outpatient ripening with a transcervical Foley's catheter. All women were then admitted to the labor ward on the following day. Patient satisfaction was evaluated using three separate surveys. The first two surveys, Six Simple Questions and Lady-X, were previously validated. The third survey used visual analog scales to assess overall pain experienced during Foley's placement, overall pain experienced during labor, how likely they would be to choose the same type of care for their next pregnancy, and how likely they would be to recommend their method of cervical ripening to friends/family.Results From May 2016 to October 2017, 129 women were randomized (outpatient, 65; inpatient, 64). Based on survey results, there was no difference in satisfaction between outpatient and inpatient cervical ripening with transcervical Foley's catheterization, with high satisfaction in both groups. Patients in both the outpatient and inpatient groups would choose the same type of care for their next pregnancy (on a scale of 1–7, median (25th–75th percentile): 7 [7–7] vs. 7 [6–7], respectively, p = 0.75) and would be very likely to recommend their method of induction to a friend or family member (on a scale of 0–100, 99 [80–100] vs. 99 [65–100], respectively, p = 0.60).Conclusion Parous women's satisfaction does not differ between inpatient and outpatient cervical ripening with transcervical Foley's catheterization.Key Points
Keywords: cervical ripening; transcervical Foley's catheter; induction of labor; outpatient cervical ripening; patient satisfaction